We Are All in This Together: Teacher Preparation, Lesson Planning, and Aiding Classroom Teachers During an Emergency School Shutdown - Aaron Rife (The Advocate, 2020)
This essay documents the attempt by a small group of student teachers in a secondary History/Government Education program to do something meaningful with their skills when buildings closed in early 2020 in a state of emergency and instruction was shifted to homes. Our solution was to create a digital classroom to share lessons and teaching materials for teachers to use as they grappled with distance learning.
Keywords: online lessons; resources for teachers; student teaching; teacher preparation